A Dietitian-Led Vegan Program May Improve GlycA, and Other Novel and Traditional Cardiometabolic Risk Factors in Patients With Dyslipidemia: A Pilot Study - Chiu, Tina H. T.; Kao, Yun-Chun; Wang, Ling-Yi; Chang, Huai-Ren; Lin, Chin-Lon (Frontiers in Nutrition, 2022)
Background: Systematic inflammation and lipid profiles are two major therapeutic targets for cardiovascular diseases. The effect of a nutritionally balanced vegan diet on systematic inflammation and lipoprotein subclass awaits further examination. Objective: To investigate the change in novel and traditional cardiometabolic risk factors before and after a dietitian-led vegan program, and to test the bioavailability of vitamin B12 in Taiwanese purple laver as part of a vegan diet. Design: A one-arm pilot intervention study. Participants/setting: Nine patients with dyslipidemia participated in this 12-week vegan program. Main outcome measures: Nuclear Magnetic Resonance (NMR) detected GlycA signal (systematic inflammation) and lipoprotein subclass (atherogenicity), trimethylamine N-oxide (TMAO), and other cardiometabolic risk factors. Statistical analyses performed: Wilcoxon signed-rank test. Results: In this 12-week vegan intervention emphasizing whole foods, systematic inflammation improved as indicated by a reduction in GlycA (median: -23μmol/L, p=0.01). LDL-cholesterol (median -24mg/dL, p=0.04) and LDL-particles (median -75nmol/L, p=0.02) both decreased significantly. VLDL and chylomicron particles showed a decreasing trend (-23.6 nmol/L, p=0.05). Without caloric restriction, BMI (-0.7kg/m2, p=0.03), waist circumferences (-2.0cm, p<0.001), HbA1c (-0.2%, p=0.02) and HOMA-IR (-0.7, p=0.04) have all improved. Change in TMAO and vitamin B12 status as measured by holo-transcobalamin appeared to depend on baseline diets, TMAO, and vitamin B12 status. Conclusions: A dietitian-led vegan program may improve systematic inflammation and other novel and traditional cardiometabolic risk factors in high risk individuals.